2021
DOI: 10.3390/molecules26092529
|View full text |Cite
|
Sign up to set email alerts
|

Dipterocarpus tuberculatus Roxb. Ethanol Extract Has Anti-Inflammatory and Hepatoprotective Effects In Vitro and In Vivo by Targeting the IRAK1/AP-1 Pathway

Abstract: Dipterocarpus tuberculatus Roxb. has been used traditionally as a remedy for many diseases, especially inflammation. Therefore, we analyzed and explored the mechanism of the anti-inflammatory effect of a Dipterocarpus tuberculatus Roxb. ethanol extract (Dt-EE). Dt-EE clearly and dose-dependently inhibited the expression of pro-inflammatory cytokines such as IL-6, TNF-α, and IL-1β in lipopolysaccharide (LPS)-treated RAW264.7 cells. Also, Dt-EE suppressed the activation of the MyD88/TRIF-mediated AP-1 pathway an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, little is known about the exact effect of TNF-α on P-gp in the placenta. Previous studies have revealed that 16) and the influence of inflammatory factors, particularly TNF-α (12,17). In this study, we found that rTNF-α induced upregulation of P-gp expression and binding activity to the AP-1 consensus DNA binding sequence, while the effects were attenuated by pretreatment with inhibitors of AP-1 (SR11302) or P-gp (SP600125).…”
Section: Discussionmentioning
confidence: 52%
“…However, little is known about the exact effect of TNF-α on P-gp in the placenta. Previous studies have revealed that 16) and the influence of inflammatory factors, particularly TNF-α (12,17). In this study, we found that rTNF-α induced upregulation of P-gp expression and binding activity to the AP-1 consensus DNA binding sequence, while the effects were attenuated by pretreatment with inhibitors of AP-1 (SR11302) or P-gp (SP600125).…”
Section: Discussionmentioning
confidence: 52%
“…This plant's heartwood contains several quinone analogs that are considered antioxidants. Several studies have reported that this plant reduces NF-mediated inflammation [44]. Jung et al (2022) coated Ti implants with MED, a natural plant extract.…”
Section: Dipterocarpus Tuberculatusmentioning
confidence: 99%
“…Of the 69 keruing species, twenty can produce oil with medicinal and fragrance properties (Boer and Ella 2001). Keruing oil contains several chemical compounds such as humulene, sesquiterpene alcohol (Aslam et al 2015), oleanilic acid (Senathilake et al 2017), and vaticaffinol (Chen et al 2017), which are useful as diuretic drugs, wound infections (Kim et al 2021), inflammatory symptoms (Yang 2013), gout (Chen et al 2017) and antifilariae (Senathilake et al 2017).…”
Section: Introductionmentioning
confidence: 99%